Review of the Dispute Between Coconut Farmers and Palm Oil Estates Regarding the Population Explosion of Coconut Beetle in Inderagiri Hilir Regency - Syamsi Mahdi; Saripah Ulpah; T.Edy Sabli; Supatmi (International Conference On Law And Social Sciences, 2024)
Indragiri Hilir is one of the regency in Riau Province – Indonesia; widely acclaimed as world coconut spread. More than a half of populations in this area depend on coconut plantation. However, a devastating population outbreak of Oryctes rhinoceros, one of coconut pest known as invasive spesies has been causing significant loss. This problems often provoked conflict between coconut farmer and oil palm estates. Issues regarding problems related to the pest outbreaks have been going on for years and publicities concerning the issues are numerous. However there are not many scientific reports to support comprehensive approach that would resulted in sustainable management of the pest. Therefore, the aim of the paper is to gain attention and support toward comprehensive approach and sustainable management of the invasive pest. The objectives of the paper is to elucidate big picture of condition and related factors causing the pest outbreak. In this paper, information and data regarding condition of public coconut plantation are presented and discussed based on publicities and the previous study conducted in one of the area affected by the pest outbreak. The study was conducted by evaluating the chronology of the infestation outbreak and by sampling of the pest population in distance to the suspected source of the infestation. Overall studies revealed that the pest outbreak correlated with the environmental change that increasing habitat carrying capacity for the pest. Solution given however has not been sufficient to address the problem in sustainable manner. Therefore integration of education, application of comprehensive approaches and law enforcement of regulation is needed involving the stakeholders to enable sustainable pest management that would ensure the coconut in this area remain” the tree of life” for the society.